Comparação de Sistemas de Avaliação de Dietas para Bovinos no Modelo de Produção Intensiva de Carne. Suplementação do Pasto para Vacas na Estação Seca - Sampaio, Alexandre Amstalden Moraes [UNESP]; De Brito, Rodolfo Marques; De Aguiar, Luciano Luz Morgan; Junior, Paulo Rossi; Da Cruz, Geraldo Maria; Alencar, Maurício Mello; Barbosa, Pedro Franklin; Barbosa, Rogério Taveira (My University, 2001)
Thirty Canchim cows, averaged 471 kg of body weight and 50 months old, were fed with supplement during the dry season of 1998, in order to evaluate the precision of the predicted performance for different systems of diet evaluation. The supplements were composed of corn silage, corn grain, citrus pulp, cottonseed meal, soybean meal and whole soybean, in agreement with the recommendations of the Metabolizable Protein System (MP); Cornell Net Carbohydrate and Protein System (CNCPS); and Intestine Digestible Protein System (PDI), for body weight maintenance. The daily body weight change obtained did not differ among treatments CNCPS, MP and PDI, with 0.34; 0.33; and 0.19 kg/head, respectively. When the meat production was the sole objective, the economic analysis revealed R$22.00; R$-44.73; and R$47.27/ha/year for MP, CNCPS and PDI systems, respectively. It was concluded that the adjusted supplements provided compatible results with the estimated animal performance.
Comparison of Diet Evaluation Systems for Cattle in an Intensive Beef Production Model. Supplementation of Pastures to Cows in the Dry Season
Keywords: Beef cattle; Corn silage; Cottonseed meal; Requirements; Soybean meal